Analisis Ketimpangan Pengeluaran Konsumsi Antar Kabupaten/Kota di Sumatera Selatan - Rifki, Muhammad; Marwa, Taufiq; Yulianita, Anna (Jurnal Informatika Ekonomi Bisnis, 2025)
This research aims to analyze the inequality of per capita consumption expenditure in South Sumatra, the influence of per capita GRDP, education level, population dependency ratio, and Human Development Index among districts/cities in South Sumatra during the period 2012-2023. The research method used is quantitative, with a regression analysis approach to test hypotheses about the relationship between the mentioned variables. Data were obtained from official sources of the South Sumatra Statistics Indonesia (BPS), covering consumption expenditure inequality, education level percentage, population dependency ratio, and the Human Development Index. The results of the analysis show that districts/cities in South Sumatra are categorized as moderately unequal between 0.25-0.35, however, Pali Regency, Musi Rawas Utara Regency, and Musi Rawas Regency have low inequality values < 0.25, while Palembang City and Lubuk Linggau City are almost approaching the very unequal criteria with values of 0.34 and 0.33 respectively. In the estimation of the multiple regression model from 4 (four) independent variables, there are 3 (three) variables that significantly influence per capita consumption expenditure, namely: Population Education Percentage (ED), Population Dependency Ratio (DR), and Human Development Index (IPM).